Itzhak : a boy who loved the violin - Newman, Tracy, 1971- (Abrams Books for Young Readers, 2020)
"Before becoming one of the greatest violinists of all time, Itzhak Perlman was simply a boy who loved music. Raised by a poor immigrant family in a tiny Tel Aviv apartment, baby Itzhak was transformed by the sounds from his family's kitchen radio--graceful classical symphonies, lively klezmer tunes, and soulful cantorial chants. The rich melodies and vibrant rhythms spoke to him like magic, filling his mind with vivid rainbows of color. After begging his parents for an instrument, Itzhak threw his heart and soul into playing the violin. Despite enormous obstacles--including a near-fatal bout of polio that left him crippled for life--Itzhak persevered, honing his extraordinary gift. When he performed on the Ed Sullivan Show sat only 13, audiences around the world were mesmerized by the warmth, joy, and passion in every note. Gorgeously illustrated with extensive back matter, this picture-book biography recounts Itzhak's childhood journey--from a boy with a dream to an internationally acclaimed violin virtuoso." -- Amazon.com